What Do Employees Know? Evidence from a Social Media Platform - Huang, Kelly; Li, Meng; Markov, Stanimir (The Accounting Review, 2020)
ABSTRACT We use employee predictions of their companies' six-month business outlook from Glassdoor.com to assess the information content of employee social media disclosures. We find that average employee outlook is incrementally informative in predicting future operating performance. Its information content is greater when the disclosures are aggregated from a larger, more diverse, more knowledgeable employee base, consistent with the wisdom of crowds phenomenon. Average outlook predicts bad news events more strongly than good news events, suggesting that employee social media disclosures are relatively more important as a source of bad news. Consistent with the organizational theory, we find systematic differences in the quantity and nature of the information in employee disclosures when the disclosures are grouped based on employee attributes and job responsibilities. Finally, average outlook predicts future returns of firms that attract less attention by analysts and investors, suggesting that investors in these firms use outlook inefficiently.